Automatic dry battery changer - Lee Eee Chin (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
This project proposes a prototype of an automatic battery charger which is more advanced than normal battery charger in todays industry. Nowadays, battery is the most significant device being utilized in the portable product. The automatic battery charger will stop automatically to charge battery when the level of charged is full. Thus, it can extend life span of the battery. Whereas the normal battery charger do not have this kind of features. This kind of smart battery charger would work for commercial use due to inexpensive spending budget. The charger can provide prolonged life of battery which will prevent it overcharging as well as leaking. This battery charger projects consists of some simple electronic component, such as capacitor, operational amplifier, relay contact, resistor with different value, voltage regulator, timer IC and NPN transistor. Battery charge level is displayed by Light-Emitting Diode (LED). This project is able to charge 12V battery with different ampere hour of capacity. The proposed charger circuit is designed and simulated by Proteus ISIS 7 Professional software. Besides that, the operation of automatic battery charger circuit is analyzed and verified. Finally, a prototype automatic battery charger circuit is developed. The functionality of automatic switching is observed throughout the experimental. The analysis results found that it is able to switch off and on automatically when battery level reached certain level.